Investigation of Intercalation of Sodium-Montmorillonite with Octadecyl Trimethyl Ammonium Bromide Surfactant - Chanra J.B Soegijono (Jurnal Vokasi Indonesia, 2017)
Sodium-montmorillonite (Na+-MMT) was intercalation modified with octadecyl trimethyl ammonium bromide (OTAB) in aqueous suspension via an ion exchange mechanism. Fourier transform infrared spectroscopy (FTIR) study indicates that OTAB is successfully intercalated into Na+-MMT layers and/or adsorbed on the surface of Na+-MMT. X-ray diffraction (XRD) analysis revealed that the interlayer spacing of the Na+-MMT was extended with the content of OTAB increasing, and the maximum spacing can reach about 3.80 nm. Results of scanning electron microscopy (SEM) analysis reveals the morphologies change from spherical-like particles to high-aspect ratio flakes after modification. Different configurations of OTA+ chains within MMT interlayer are proposed based on the above analysis. The results of contact angle and the dispersion analysis show that the surface wettability of Na+-MMT is converted from hydrophilic to organophilic.